Science, Technology and Research Network (STARNET) - Walter R. Blados (Issues in Science and Technology Librarianship)
The article discusses a science, technology and research network  called STARNET, developed by the Information Management Committee of the NATO Research Technology Agency. The purpose of this network is to facilitate access to information elements existing worldwide, in terms of science, technology and overall research. STARNET is designed as a virtual library for these information elements; it is a database of web-based data sources, which will allow comprehensive and sophisticated searches.